Sufism and Religious Moderation: The Internalization Process in Thoriqoh Syadziliyah Al Masudiyah Jombang - Hasan, Moch. Sya'roni; Mujahidin, Mujahidin (Nazhruna: Jurnal Pendidikan Islam, 2023)
This research explores the internalization of Sufism values ​​in forming an attitude of religious moderation in the Thoriqoh Syadziliyah Al Masudiyah Jombang Congregation. Using a qualitative case study approach, this research analyzes the recitation of Selapanan Ahad Legi to deepen religious understanding and practice of Sufism values. The main values ​​taught in Sufism include zuhud, tawakkal, sincerity, patience, gratitude, love, willingness, tolerance, and non-violence. The internalization process is done through active learning methods such as lectures, group discussions, sharing experiences, direct demonstrations, and personal advice from ustadz/murshid. These methods involve the congregation's cognitive, affective, and psychomotor domains to form complete and permanent behavioral changes. By internalizing the values ​​of Sufism, it is hoped that the congregation will develop a moderate attitude toward religion, reflected in a simple lifestyle, optimism, sincere quality of worship, strong fighting power, not easily provoked, grateful, loving others, and tolerant of diversity. Recitation activities have proven effective in internalizing Sufism values ​​and forming moderate attitudes in the congregation. Therefore, recitation activities must be developed as an agent of social change towards a moderate Muslim society.